Single Phase Permanent Magnet Low Speed Synchronous Motor - Gao Lianxue; Sun Diansheng (Institute of Advanced Engineering and Science, 2013)
In order to acquire a better cognition to the single phase permanent magnet low speed synchronous motor and validate the correctness of the motor mathematical model, the performances of the motor are tested with the single phase permanent magnet low speed synchronous motor whose type is 70TDY4, the corresponding simulations are done too. The resistance and the inductance of the single phase permanent magnet low speed synchronous motor are measured. According to the data of experiments and simulations, the static characteristics of the single phase permanent magnet low speed synchronous motor with the changes of the phase shift resistance and the phase shift capacitance are analysed, the results of experiments and simulations prove the correctness of the mathematics model. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2396